Stress and salivary cortisol in emergency medical dispatchers: A randomized shifts control trial. - Sarah Bedini; François Braun; Laurence Weibel; Michel Aussedat; Bruno Pereira; Frédéric Dutheil (PLoS ONE, 2017)
Stress at work is a public health concern. Phone operators in emergency medical dispatch centers are particularly at risk. We aimed to demonstrate that the most stressful time for emergency medical dispatchers is the shift when they receive emergency incoming calls, with cortisol as a biomarker of stress. For each emergency medical dispatcher, we measured outcomes over a control day and during three types of shift: Incoming emergency call, Dispatch and Re-assessment. The pattern of shifts was randomized. Saliva was sampled every 15 minutes for 2 hours, i.e. 6 consecutive times, starting 15 minutes after the first life-and-death incoming emergency call between 2 and 5 pm during three types of shift. We measured saliva cortisol every 2 hours over a control day, from 7am to 9pm. Perceived stress was assessed by a visual analog scale. We recruited 22 phone operators aged 36.4+/-10.8 years old (14 women and 8 men). Cortisol values were higher during the Incoming emergency call shift than during the Dispatch (p = .04) and Re-assessment (p = .04) shifts. The increase in cortisol levels was greater in men than in women (p = .009). There were no differences between control values and those of the three shifts. The kinetics of cortisol increased with greater perceived stress overall (p < .001) and for each type of shift (Incoming emergency call, p = .02; Dispatch p = .03; Re-assessment: p < .001). The kinetics of cortisol in response to incoming emergency calls was greater when the call was an absolute emergency (p = .03), and also tended to further increase when a subsequent absolute incoming emergency call was received (p = 0.07). In conclusion, the incoming emergency call shift carries particular risk for dispatchers, who have greater perceived stress and a greater increase in cortisol levels.